PERAN STAKEHOLDER DALAM IMPLEMENTASI EKONOMI PEMBANGUNAN PADA PENGELOLAAN SAMPAH : THE ROLE OF STAKEHOLDERS IN THE IMPLEMENTATION OF DEVELOPMENT ECONOMICS IN WASTE MANAGEMENT - Avelia, Rizky Renuka; Mukhlis, Imam (e-Journal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to analyze the role of stakeholders in the implementation of circular economy in waste management in Jongbiru Village, Gampengrejo District, Kediri Regency. This village was chosen because it is the location of TPS 3R implementation as a solution to environmental problems, especially waste, through a circular economy approach. The method used is qualitative with a case study approach. Data were obtained through observation, in-depth interviews, and documentation studies. The results showed that the implementation of circular economy in TPS 3R Jongbiru has been running although it still faces various obstacles, such as limited human resources and not optimal periodic evaluation. The role of stakeholders is divided into several functions: TPS 3R managers as field implementers, academics as innovation accelerators, Rotation Institute as facilitators and policy creators, and village government as coordinators and local policy makers. Collaboration between stakeholders is a key factor in the sustainability of the 3R-based waste management program and circular economy. This research concludes that multi-stakeholder synergy is needed so that the village waste management model can become an efficient, sustainable system, and contribute to the achievement of sustainable development goals (SDGs).